Factors affecting fill removal from horizontal well during colied tubing cleanout operation - Pao, W.K. (EDP Sciences, 2014)
Coiled Tubing (CT) is extensively used in oil industry to clean the wellbore to increase the productivity of oil/gas well by removing the fill/sand downhole. Well cleanup operation for low bottom hole pressure is problematic and common cleanout fluids are not effective as a circulation fluid due to severe pressure losses and low suspension capability. The use of foam as cleaning agent has become more popular due to its low density and high viscosity. The objective of this paper is to investigate the factor effecting on fill concentration and pressure loss during horizontal wellbore cleanup operation at different CT/Annulus diameter ratios using Herschel Buckley viscosity model. Results showed that foam quality has the significantly high effect on fill concentration as compared to foam velocity. It is noticed that diameter ratio has high effect on particle removal when foam quality is 70. Surprisingly, it is found that the effect of diameter ratio on fill concentration decreases when foam quality is 90. Â© 2014 Owned by the authors, published by EDP Sciences.